Behavioral Model of the Risk of HIV/AIDS in Gorontalo Transmission Adolescents - ., Irwan; Anwar, Ayub Irmadhani; Katili, Deliyana I; Mokodompis, Yasir (Journal of Ecohumanism, 2025)
In 2023, a total of 198 HIV/AIDS cases were reported in Gorontalo Province, comprising 89 males and 109 females, with 87% falling within the productive age group of 25-35 years. This observational research employed a cross-sectional approach. Pathway analysis was conducted using Structural Equation Modelling with AMOS 8.50. The study examined variables including beliefs, intention, and risky behavior. A total of 200 samples were collected from Gorontalo City. The pathway analysis model for female teenagers engaging in risky behaviors revealed a significant influence of intention (p = 0.001), which was further influenced by beliefs (p = 0.001) and religious piousness (p = 0.001). The model of risky behavior related to HIV/AIDS in female teenagers was notably influenced by intention and religious piousness.